Lymphedema After Covid-19: Case Report of a Patient with a History of Mastectomy Who Remained Asymptomatic for 35 Years - Pereira de Godoy, MD, PhD, Jose Maria; Pereira de Godoy, MD, Ana Carolina; Pereira de Godoy, MD, Henrique Jose (International Journal of Innovative Research in Medical Science, 2025)
This paper reports on a case of upper limb lymphedema 20 days after the diagnosis of Covid-19 in a patient with a history of mastectomy who had remained asymptomatic for 35 years. The medical assessment revealed lymphedema, with no history of infection, trauma, physical effort or any other triggering factor of edema. Multisegmented bioimpedance performed with the InBody 10 equipment confirmed lymphedema in the left limb (2.65 liters in left limb vs. 2.06 liters in right limb).